The unknown - Graham, Heather (Graham, Heather. Krewe of hunters., 2021)
The newest member of the Krewe of Hunters elite paranormal team, FBI agent Ryder Stapleton must enlist the help of a beautiful museum curator with an otherworldly ability to track down a serial arsonist setting first to the streets of New Orleans.